Development, hotspots, and trend directions of research on green production behavior of farmers based on CiteSpace and VOSviewer visual analysis - Zhang, Bin; Mao, Wenyi; Hu, Zhen (Frontiers in Nutrition, 2025)
IntroductionPromoting the popularization of green production behavior among farmers is the key to achieving sustainable agricultural development, guaranteeing food security and protecting the ecological environment.MethodsBased on the Web of Science core database, this study used CiteSpace and VOSviewer to conduct a bibliometric analysis of 697 literatures on green production behaviors of farmers from 2000 to 2024, aiming to sort out the development history and characteristics of this research field.Results and discussionThe results show that the number of literature in this field continues to grow, and the studies are concentrated in the field of environmental sciences, and most of them are published in Sustainability journals; China is the largest contributor to the literature in this field, and it cooperates closely with the United States, and the research institutes and authors are mainly from the Chinese institutions of higher education; the studies are mainly focused on the three dimensions of the behavioral drivers, the development of the theoretical models, and the evaluation of the benefits of the implementation. The current research hotspots include behavioral implementation benefits, influencing factors of behavioral adoption, green production methods, and the impact of green revolution on behavioral adoption. This study systematically summarizes the research hotspots, challenges and future development directions in the field of farmers' green production behaviors, and provides an important reference for subsequent theoretical research and innovative practices.